Fabricating 3D Structures by Combining 2D Printing and Relaxation of Strain. Issue 1 (21st August 2018) - Cafferty, Brian J.; Campbell, Victoria E.; Rothemund, Philipp; Preston, Daniel J.; Ainla, Alar; Fulleringer, Nicolas; Diaz, Alina C.; Fuentes, Alberto E.; Sameoto, Dan; Lewis, Jennifer A.; Whitesides, George M.
Abstract: This paper describes the fabrication of elastomeric three‐dimensional (3D) structures starting from two‐dimensional (2D) sheets using a combination of direct‐ink printing and relaxation of strain. These structures are fabricated in a two‐step process: first, elastomeric inks are deposited as 2D structures on a stretched elastomeric sheet, and second, after curing of the elastomeric inks, relaxation of strain in the 2D sheet causes it to deform into a 3D shape. To predict bending of elastomeric objects fabricated with this technique, a simple mechanical model is developed. The strategy of using initially 2D materials to fabricate 3D structures offers four new features that complement digital fabrication techniques. (i) It provides a simple route to create shapes with complex curves, suspended features, and internal cavities. (ii) It is a faster method of fabricating some types of shapes than "conventional" 3D printing, because the features are printed in 2D. (iii) It forms surfaces that can be both smoother, and structured in a way that is not compatible with layer‐by‐layer processing. (iv) It forms structures that can be deformed reversibly after fabrication by reapplying strain. This paper demonstrates these features by fabrication of helices, structures inspired by cubes and tables, "pop‐up" structures, and soft grippers. Abstract : Printing two‐dimensional (2D) structures on stretched, elastomeric substrates forms three‐dimensional (3D) structures upon relaxation. This technique allows for precise control over the curvature of 3D structures by exact ink patterning, provides a number of advantages over commonly used technologies for 3D printing, and is attractive for rapid prototyping and fabrication of structures that are deformable and/or contain hollow components.